1974
DOI: 10.1093/nar/1.11.1579
|View full text |Cite
|
Sign up to set email alerts
|

A model for particulate structure in chromatin

Abstract: A model is proposed for the structure of nuclease-resistant chromatin particles. The model is novel in that it proposes that the DNA in such a particle is wound about a protein core, made up of the hydrophobic regions of histone molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(84 citation statements)
references
References 29 publications
5
79
0
Order By: Relevance
“…Our particular model for chromatin structure, proposed in Fig. 6, is consistent with the general view of chromatin structure recently elaborated by others (13)(14)(15). However, it extends these models both in indicating how histones might fold the nuclease-particles by crosslinking the DNA, and in accommodating the fact that histone aggregates, as revealed in the nuclease-particles, are clearly heterogeneous.…”
Section: Nh2supporting
confidence: 90%
“…Our particular model for chromatin structure, proposed in Fig. 6, is consistent with the general view of chromatin structure recently elaborated by others (13)(14)(15). However, it extends these models both in indicating how histones might fold the nuclease-particles by crosslinking the DNA, and in accommodating the fact that histone aggregates, as revealed in the nuclease-particles, are clearly heterogeneous.…”
Section: Nh2supporting
confidence: 90%
“…However, a simple supercoil loop of about 680 A in length (200 base pairs) of DNA duplex would by far exceed the size of a nucleosome. Our results are, therefore, better accounted for by a model of nucleosome structure in which the DNA would be folded (kinked, 30), rather than by models in which the DNA would be regularly wound in a superhelical form (29,31).…”
Section: Experiments and Resultsmentioning
confidence: 89%
“…Alternatively, a combination of intranucleosomal unwinding and supercoiling could cause the torsional alteration. Current models of nucleosome structure involve wrapping of the DNA around a protein core (28)(29)(30)(31). However, a simple supercoil loop of about 680 A in length (200 base pairs) of DNA duplex would by far exceed the size of a nucleosome.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Subunits from higher eukaryotes contain two copies each of histones H2A, H2B, H3, and H4 associated with about 140 base pairs of DNA (12,14). Recent neutron diffraction studies (15) have confirmed earlier proposals (10,11) that these histones form a "core" about which the unit length of DNA is wrapped. Lysine-rich histones HI (and H5 in erythrocytes) appear to be associated primarily with the "spacer" DNA, 30-60 base pairs long, between globular subunits (14,16,17).…”
mentioning
confidence: 84%
“…Interphase chromatin fibrils of higher eukaryotes have a "beaded string" structure consisting of repeated arrays of globular particles (about 100 A diameter) connected by thin nucleoprotein filaments (9)(10)(11)(12). Nucleases cleave these interconnecting regions, producing individual "subunits" and larger oligomeric nucleoprotein units that can be readily isolated (12,13).…”
mentioning
confidence: 99%